2008
DOI: 10.1111/j.1474-9726.2008.00436.x
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced glycogenesis is involved in cellular senescence via GSK3/GS modulation

Abstract: SummaryGlycogen biogenesis and its response to physiological stimuli have often been implicated in age-related diseases. However, their direct relationships to cell senescence and aging have not been clearly elucidated. Here, we report the central involvement of enhanced glycogenesis in cellular senescence. Glycogen accumulation, glycogen synthase (GS) activation, and glycogen synthase kinase 3 (GSK3) inactivation commonly occurred in diverse cellular senescence models, including the liver tissues of aging F34… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
79
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 77 publications
(89 citation statements)
references
References 57 publications
9
79
1
Order By: Relevance
“…The putative role of GSK3β for sustaining cancer cells survival may therefore be due in part to effects on hTERT expression and telomerase activity, as well as on cellular senescence. The latter effect may be consistent with a recent report that enhanced glycogenesis is directly linked to cellular senescence through modulation of GSK3α/β and glycogen synthase (45).…”
Section: Discussionsupporting
confidence: 93%
“…The putative role of GSK3β for sustaining cancer cells survival may therefore be due in part to effects on hTERT expression and telomerase activity, as well as on cellular senescence. The latter effect may be consistent with a recent report that enhanced glycogenesis is directly linked to cellular senescence through modulation of GSK3α/β and glycogen synthase (45).…”
Section: Discussionsupporting
confidence: 93%
“…However, we also observed that knocking down SREBP-1 below the level of control cells by using high dose siRNA also induced growth arrest (data not shown), suggesting that the well balanced regulation of lipogenesis is required to maintain normal cellular function, and the fine control of SREBP-1 activation is essential to control senescence. In addition, our previous study proved that glycogen synthase kinase 3 (GSK3) is commonly inactivated by being phosphorylated and is also importantly involved in all the cell senescence systems (DFO-and H 2 O 2 -induced, and replicative senescence) employed in this study (27). GSK3 is known to modulate SREBP1 activity through phosphorylation-mediated ubiquitination (21).…”
Section: Discussionmentioning
confidence: 72%
“…Organelles of Senescent Cells-First, we examined changes in mass of all cellular organelles, especially membranous ones, in stressinduced senescence triggered by DFO and H 2 O 2 as described previously (7,26,27). Subcellular organelles were stained with organelle-specific fluorescent dyes, and their masses were estimated by flow cytometric analysis (Fig.…”
Section: Overall Mass Increases In Membranous Subcellularmentioning
confidence: 99%
“…Senescence-associated ␤-Galactosidase Activity Staining-SA-␤-gal activity was assayed at pH 6.0 as described previously (38). The stain was visible for 12 h after incubation at 37°C.…”
Section: Methodsmentioning
confidence: 99%